(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
It is no exaggeration to say that one of the most pressing issues today is the spiritual and moral upbringing of young people at school through singing, opera and ballet. This article discusses the importance of opera and ballet in educating the younger generation.